Analisis Visual Sosial Toleransi Dalam Film Bumi Itu Bulat - Fathoni, Muhammad; Dewi, Ni Putu Sinta; Khairunnisa; Vinastika, Baiq Yayi (CV Insan Kreasi Media, 2024)
This study aims to describe the visuals of tolerance in Indonesia in the Bumi Itu Bulat movie. The phenomenon of mutual respect, acceptance and mutual understanding in the Bumi Itu Bulat movie is an adhesive for diversity and provides its own message in the social world for society so it is worthy of study. This study uses content analysis methods with a semiotic approach to analyze the tolerance values contained in the Bumi Itu Bulat movie. The results found that there are visuals in the form of active tolerance and passive tolerance. Active tolerance is the ability to take concrete actions to create good social relations by volunteering for violent disasters, as well as preventing the destruction of houses of worship of other religions. Passive tolerance is the ability to accept and respect differences of opinion, views, behavior and habits with the visual of living together peacefully, personal awareness involved in getting along in every social interaction.